2012
DOI: 10.1121/1.4765304
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the effects of roughness scattering on reflection loss measurements

Abstract: Seafloor reflection loss and roughness measurements were taken at the Experimental Validation of Acoustic Modeling Techniques experiment in 2006. The magnitude and phase of the reflection loss was measured at frequencies from 5 to 80 kHz and grazing angles from 7° to 77°. Approximately 1500 samples were taken for each angle. The roughness was measured with a laser profiler. Geoacoustic parameters such as water and sediment sound speed and density were measured concurrently. The reflection loss data were compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…4 and 5, the average value is around -10 dB, consistent with medium sand. [4] Lower values at shorter ranges are consistent with a silt or mud. The reflection coefficient data appear uncorrelated with both bathymetry and the highfrequency backscatter.…”
Section: B Reflection Coefficient and Scattering Measurementssupporting
confidence: 72%
“…4 and 5, the average value is around -10 dB, consistent with medium sand. [4] Lower values at shorter ranges are consistent with a silt or mud. The reflection coefficient data appear uncorrelated with both bathymetry and the highfrequency backscatter.…”
Section: B Reflection Coefficient and Scattering Measurementssupporting
confidence: 72%
“… 35 The second most common behaviour is the scattering effect from the material that arises due to factors such as morphologies of surface and wall roughness and thickness. 23 The glass wafers used as sealing layers on either side of the silicon wafer effectively worked as the X-ray windows and were of 175 μm thickness ( Fig. 3b ).…”
Section: Resultsmentioning
confidence: 99%
“…The microfabrication technique is also a dominant consideration for spectroscopy techniques, such as XAS, as the surface is required to be smooth to avoid/reduce any undesirable scattering effects from a materials surface roughness. 23 The material and fabrication technique considerations needed for the XAS analysis method led to the present work. A silicon–glass plasma-etched and anodically bonded microfluidic device to flow samples and study sample behaviours by interacting with high energy X-rays was developed and validated in this work.…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been shown that the best fit with experimental reflection, sound speed, and attenuation measurements occur when the sediment is assumed to behave as a poroelastic medium. 1,2 The theory of sound propagation in poroelastic media was first introduced by Biot in a series of classic papers. 3,4 This formulation was extended by Stoll and Kan and applied to the problem of wave reflection from a flat fluidporoelastic interface.…”
Section: Introductionmentioning
confidence: 99%